Assessment of Growth Enhancement Support (GES) Scheme in Anambra State, Nigeria - Hycinth U Nwalieji; C O Uzuegbunam; M. N. Okeke (Journal of Agricultural Extension, 2015)
The study assessed growth enhancement support (GES) scheme in Anambra State, Nigeria. Specifically, the study determined extent of achievement of the scheme in providing farmers with inputs; assessed farmers’ perception of changes brought about by the scheme on food production as well as access to farm inputs; determine farmers’ level of satisfaction on the scheme’s implementation processes; and identified challenges to effective implementation of the scheme. The population of the study included all rice farmers that participated in the scheme in Anambra State. Multistage, purposive and simple random sampling techniques were used in selecting a total sample size of 100 respondents. Primary and secondary sources of data were used and collected through the use of an interview schedule and the scheme’s publications. Percentage and mean were used to analyze data. The result of the findings showed that the scheme had very low performance indices in redemption of inputs. The Scheme made great changes in food productivity (M = 2.70) and farmers’ access to farm inputs (M = 2.55). Farmers had high level of satisfaction on the scheme’s implementation processes in the areas of registration process and quantity of improved seed redeemed. Major challenges identified were poverty, illiteracy, poor awareness, and poor mobile phone possession and usage. It was recommended that more awareness and adequate training be given to farmers for them to participate actively and for other farmers to join the scheme. Also there is need for the scheme to be passed into law to become policy for continuity and sustainability.